Factors Affecting the Mortality of Patients Undergoing Open Heart Surgery with Cardiopulmonary Bypass at Dr. M. Djamil General Hospital, Padang, Indonesia - Yudhi Leo Prima; Aulia Rahman; Mefri Yanni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Morbidity and mortality of patients after cardiac surgery can be influenced in the preoperative, intraoperative, and postoperative periods. This study aimed to explore factors that affect the mortality of patients undergoing open heart surgery with cardiopulmonary bypass at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This study is an analytical observational research with a cross-sectional approach and uses secondary data obtained from the medical record installation of Dr. M. Djamil General Hospital, Padang, Indonesia. A total of 57 research subjects participated in this study. Univariate, bivariate, and multivariate analyses were carried out using SPSS software. Results: The final multivariate modeling results show that the variables that influence patient mortality are EuroSCORE II (p-value=0.003) and duration of CPB (p-value=0.003). With an odds ratio of 37.21 groups, EuroSCORE II high risk had a risk of death 37.21 times higher than the low-risk group (CI 3.325 – 416.324). Meanwhile, increasing the duration of CPB by one minute increased the risk of mortality 1.02 times (CI 1.006 – 1.030). Meanwhile, there is no influence of variables (NYHA, LV function, ACC duration) on the incidence of mortality in patients undergoing open heart surgery with a machine cardiopulmonary bypass at Dr. M. Djamil General Hospital, Padang. Conclusion: EuroSCORE II affects the mortality of patients undergoing open heart surgery with CPB. The duration of CPB affects the mortality of patients undergoing open heart surgery with CPB.